Does Gut Microbial Methylglyoxal Metabolism Impact Human Physiology? - Oluwatomisono I. Akinrimisi; Kim Maasen; Jean L. J. M. Scheijen; Ina Nemet; Max Nieuwdorp; Casper G. Schalkwijk; Nordin M. J. Hanssen (Antioxidants, 2025)
Methylglyoxal (MGO) is a highly reactive dicarbonyl associated with oxidative stress, inflammation, and chronic diseases, particularly diabetic vascular complications and atherosclerosis through the formation of advanced glycation end products (AGEs). In the setting of human/host diseases, the formation of MGO has mainly been considered as the byproduct of glycolysis. Gut microbes play an important role in the development of cardiometabolic diseases. Here, we discuss a possibility that gut microbes can modulate the MGO pool within the host through (i) the alternation of the host metabolism, and (ii) direct MGO synthesis and/or detoxification by human commensal microorganisms. We also explore how dietary MGO impacts the composition of the gut microbiota and their potential role in modulating host health. This paradigm is highly innovative, with the current literature providing observations supporting this concept. Targeting the gut microbiome is emerging as an approach for treating cardiometabolic diseases through dietary, pre-, pro-, and postbiotic interventions, faecal microbiota transplantations, and the use of small molecule inhibitors of microbial enzymes. This can be a novel strategy to reduce MGO stress in the setting of cardiometabolic diseases and lowering the burden of diabetic complications and cardiovascular disease.